The Interplay of Language Policy and Learner Agency in Multilingual Educational Contexts - Fachrullah, Muhammad Fauzy; Alam, Akmal (LIER: Language Inquiry & Exploration Review, 2025)
Purpose: This study aims to explore the interplay between language policy and learner agency in multilingual educational contexts, focusing on how institutional policies influence learners' language behaviors, academic performance, and overall agency. Subjects and Methods: The research involved 300 secondary school students from multilingual educational settings, with 120 students whose home language matched the medium of instruction and 180 whose home language differed. A mixed-methods approach was employed, combining qualitative interviews and focus group discussions with quantitative surveys and performance data. The study examined learners' perceptions of language policies, their agency indicators (e.g., language control, switching frequency, participation), and academic achievement across subjects (Math, Science, Social Studies). Results: The results revealed that learners with home-instruction language alignment reported higher agency, confidence, and participation in classroom discussions. In contrast, those with mismatched home languages exhibited higher language switching and lower confidence in using their home languages. Participation in multilingual programs correlated with better academic outcomes, particularly in language proficiency and subjects like Science and Math. The study found significant correlations between supportive language policies (inclusive of home languages) and enhanced learner agency, while restrictive policies hindered agency and engagement. Conclusions: The study concludes that inclusive and flexible language policies positively influence learner agency, which in turn enhances academic achievement. Policy climates that value linguistic diversity are crucial for empowering learners, particularly those from diverse linguistic backgrounds. Addressing socio-economic inequalities is also necessary to ensure equitable educational opportunities for all students.